The relationships between consumer liking, sensory and chemical attributes of Vitis vinifera L. cv. Pinotage wines elaborated with different Oenococcus oeni starter cultures. (5th April 2013) - Malherbe, Sulette; Menichelli, Elena; du Toit, Maret; Tredoux, Andreas; Muller, Nina; Næs, Tormod; Nieuwoudt, Hélène
Abstract Background Malolactic fermentation (MLF) mediated by lactic acid bacteria (LAB) has been shown to modulate chemical and sensory attributes of wine. This study investigated the relation between consumer liking, chemical and sensory attributes of Vitis vinifera L. cv. Pinotage wines that were made over two vintages by four different lactic acid Oenococcus oeni starter cultures as well as a control treatment where MLF was prevented. Results Descriptive analysis showed that the sensory attributes buttery, caramel, vegetative flavour, fruity and nutty aroma differed significantly between the wines. These effects on the wines were not the same for the two vintages tested. Preference mapping results showed that the sensory attributes influenced the average consumer liking. The main chemical and sensory correlations found for MLF‐treated wines were related to 2, 3‐butanedione (diacetyl) with the buttery character and various esters with fruity aromas. Conclusion Although the direct effect of the bacterial starter cultures on wine sensory attributes is difficult to establish, and subject to variation over vintage, the present work suggests that the contribution of LAB starter cultures to wine sensory attributes can influence consumer liking. Selection of an MLF starter culture can thus potentially be used to develop specific wine styles. © 2013 Society of Chemical Industry